2009
DOI: 10.1097/01.aoa.0000358406.25166.32
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Caffeine Intake during Pregnancy and Risk of Fetal Growth Restriction: A Large Prospective Observational Study

Abstract: This is a repository copy of Maternal caffeine intake during pregnancy and risk of fetal growth restriction: a large prospective observational study..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…This was included in the low birth weight analysis as these formed the majority of events, but with sensitivity analysis to confirm that this did not substantially change the results. One study provided additional information on miscarriage and stillbirth separately that was incorporated into the meta-analyses [29]. One publication provided results for the association between preterm delivery and caffeine separately for small for gestational age infants and normal for gestational age infants [18].…”
Section: Literature Searchmentioning
confidence: 99%
“…This was included in the low birth weight analysis as these formed the majority of events, but with sensitivity analysis to confirm that this did not substantially change the results. One study provided additional information on miscarriage and stillbirth separately that was incorporated into the meta-analyses [29]. One publication provided results for the association between preterm delivery and caffeine separately for small for gestational age infants and normal for gestational age infants [18].…”
Section: Literature Searchmentioning
confidence: 99%
“…Detailed methods on the caffeine assessment are described elsewhere [11]. A validated caffeine assessment tool (CAT) to record habitual caffeine intake was administered at booking (8-12 weeks) by a clinical research fellow or research midwives, and completed 6 by the participants during weeks 13-28, and finally weeks 28 to the end of pregnancy.…”
Section: Caffeine Intakementioning
confidence: 99%
“…Caffeine, in particular, has received much interest in recent years. Studies have shown that maternal caffeine consumption may increase the risk of adverse pregnancy outcomes [11][12][13][14][15]. It has been suggested that women who experience nausea may be less likely to consume caffeine [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations